Needs Analysis of Project-Based English Essay Writing Teaching Materials Development - Rohmah, Ainur (Universitas Jambi, Magister Program of English Education Department, 2023)
This research used an R&D development model which was aimed at analyzing and identifying the needs of the students' learning and the development in Project-Based English essay writing teaching materials. The subjects of the research were third-semester English students and lecturers of Nurul Huda University, East OKU, South Sumatra. The research used four instruments for answering the research problems, namely the indicators of descriptive essay writing; the researcher review assesments; the experts' assesments; and students' and lecturers' interviews or questionnaires. The results showed that the needs for the development of Project-Based English essay writing teaching materials are high and various regarding to the students’ neccesities, lacks, and wants, and these needs are based on what they have been got or attained during the learning process.